2003
DOI: 10.1152/ajpendo.00478.2002
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid status, but not insulin status, affects expression of avian uncoupling protein mRNA in chicken

Abstract: Decuypere. Thyroid status, but not insulin status, affects expression of avian uncoupling protein mRNA in chicken. Am J Physiol Endocrinol Metab 284: E771-E777, 2003. First published December 10, 2002 10.1152/ajpendo.00478.2002The aim of this study was to investigate the hormonal regulation of the avian homolog of mammalian uncoupling protein (avUCP) by studying the impact of thyroid hormones and insulin on avUCP mRNA expression in chickens (Gallus gallus). For 3 wk, chicks received either a standard diet (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 40 publications
3
23
0
1
Order By: Relevance
“…Cold exposure also increases the expression of UCP in chicken muscle corroborating previous studies in mammals (Boss et al,'97a;Carmona et al,'98) and in birds (Raimbault et al, 2001;Collin et al, 2003a;Talbot et al, 2004;Ueda et al, 2005). This latter observation, in combination with previous findings based on the predominant distribution of UCP in skeletal muscle (Raimbault et al, 2001), and its induction by thyroid hormones (Collin et al, 2003b) and glucagon (the thermogenic hormone in birds) (Raimbault et al, 2001) suggest that UCP may play a pivotal role in non-shivering thermogenesis. The rapidity of leptin and UCP response to cold reported here can appear surprising, but is similar to that due to isoproterenol (non selective b-adrenergic agonist) infusion in humans (Ricci and Fried,'99) supporting a possible shortterm control of leptin and UCP gene expression in chickens.…”
Section: Discussionsupporting
confidence: 89%
“…Cold exposure also increases the expression of UCP in chicken muscle corroborating previous studies in mammals (Boss et al,'97a;Carmona et al,'98) and in birds (Raimbault et al, 2001;Collin et al, 2003a;Talbot et al, 2004;Ueda et al, 2005). This latter observation, in combination with previous findings based on the predominant distribution of UCP in skeletal muscle (Raimbault et al, 2001), and its induction by thyroid hormones (Collin et al, 2003b) and glucagon (the thermogenic hormone in birds) (Raimbault et al, 2001) suggest that UCP may play a pivotal role in non-shivering thermogenesis. The rapidity of leptin and UCP response to cold reported here can appear surprising, but is similar to that due to isoproterenol (non selective b-adrenergic agonist) infusion in humans (Ricci and Fried,'99) supporting a possible shortterm control of leptin and UCP gene expression in chickens.…”
Section: Discussionsupporting
confidence: 89%
“…By increasing membrane proton conductance, avUCP should decrease the efficiency of the oxidative phosphorylation process, thereby diverting the energy from ATP synthesis to thermogenesis. In line with this idea, avUCP level increased in a situation where energy efficiency is decreased such as in triiodothyronine-treated chickens (Collin et al, 2003b) whereas it was reported to be decreased in hypothyroid chickens (Collin et al, 2003b) or in long-term fasted penguins (Rey et al, 2008) when energy efficiency would increase. Interestingly, a chicken line selected for its low efficiency of food utilization for growth displayed a higher level of avUCP mRNA in their skeletal muscle than a chicken line divergently selected for its high food efficiency (Raimbault et al, 2001;Ojano-Dirain et al, 2007).…”
Section: Discussionmentioning
confidence: 72%
“…Unlike in muscle, however, reduced thyroid levels did not influence PGC1α gene expression in liver, where it may be induced instead by cAMP and glucocorticoids to controls gluconeogenesis (Yoon et al, 2001). In addition to stimulating PGC1α expression and thereby mitochondrial capacity, thyroid hormones can also control the activity of ANT and UCP (Collin et al, 2003). The downregulation of ANT in liver after induced hypothyroidism indicates a regulatory effect of thyroid hormones on ANT.…”
Section: Discussionmentioning
confidence: 86%